(Public) Interest in Private Security Services? A debate on the Relationship between Public and Private Policing (Academic Journal of Internal Affairs, 2017)
The author provides an overview of a recently held workshop on law enforcement challenges, organized jointly by the Public Law Subcommittee and the Law Enforcement Subcommittee of the Hungarian Academy of Sciences.
Keywords: Private Security Services; law enforcement; challenges